Perlindungan Hak Asasi Manusia Bagi Perempuan Kaum Minoritas Perspektif Hukum Internasional - Nanulaitta, Hana Delvina; Baadila, Efie; Tahamata, Lucia Charlota Octovina (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Cases of human rihts violations against women of the Rohingya ethnic minority by the Myanmar army and their protection for women of the Rohingya Ethnic minority in Myanmar.Purposes of the Research: This writing aims to find out and discuss the forms of regulation and protection of human rights law regarding minority women in international law.Methods of the Research: The research method in this writing uses the type of analytical prescriptive research. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results obtained are to explain that related to human rights violations committed by the Myanmar army against women of the Rohingya ethnic minority, where in the process of enforcement and protection is not in accordance with what is done by the Myanmar government. Therefore, in order to maintain security, peace and peace together, it is necessary to have the role of world countries, especially the United Nations, ASEAN and the International Community to stop human rights violations.